Effect of Saline Water Irrigation on Properties of Vertisols and Yield of Setaria - Kubsad, V S; Hunshal, C S; Vishwanath, D P; Chimmad, V P; Mansur, C P (Annals of Arid Zone, 2016)
Effect of saline irrigation waters (1, 2,4,6,8 and 12dSm-1) on soil properties, available nitrogen, water soluble cations.and yield of setaria (Setaria italica L.) revealed that the soil EC2 gradually decreased after sowing till 61 DAS(0.71dSm-1) and it increased till 75 DAS(0.93dSm-1) and thereafter,again decreased at harvest(0.58dSm-1 The available nitrogen and phosphorus were more in surface layer after halvest and were less affected due to salinity levels. Among the water soluble cations, the concentration of K, Mg and Na increased with increasing salinity and Ca increased upto 6 dSm-1 . at both the soil depths after harvest.The grain yield increased upto 6 dSm-1 salinity level and decreased, thereafter.